The basel convention: re-visting some socio-legal issues pertaining to transboundary movement of hazardous and other wastes - Ansari, Abdul Haseeb; Jamal, Parveen; Ahmad, Muhamad Hassan (The Indian Law Institute, 2019)
The Basel Convention with the Rotterdam Convention and the Stockholm Convention provides an international regal regime for prevention and control of transboundary movement of hazardous wastes for whatever reasons. This legal regime is supplemented with the Bamako Convention prohibiting import of hazardous wastes in African countries. They have large number of memberships and are successful in achieving the underlined objectives with the application of PIC mechanism. But for certain obvious reasons, smuggling of hazardous wastes and their transboundary movement in disguise of recycling them or using them as raw materials are on the rife, especially to African, Central Asian and South Asian countries. There are a number of cases proving this. Among them, the Trafigura case of Ivory Coast is the most notable one. The paper sheds light on topical issues pertaining to the legal regime. It also looks into the probable reasons for which poor countries succumb to be used as dumping grounds. The authors suggest that the provisions of the conventions should be strictly followed and for that all countries, developing, least developed and developed, should have enough political will to properly enforce the law based on the PIC principles. They also suggest that the membership of the Basal Convention should further be increased so that the menace of transboundary movement of hazardous wastes, which infringes the sovereignty of poor sates, and violates rights of their citizens, could me alleviated.